E‐Commerce Effects on Energy Consumption: A Multi‐Year Ecosystem‐Level Assessment. (31st July 2017) - Dost, Florian; Maier, Erik
Summary: This research investigates the impact of e‐commerce on energy consumption in all four sectors of the U.S. economy (commercial, industrial, residential, and transportation), using macroeconomic data from 1992 to 2015. These data capture all the development phases of e‐commerce, as well as direct and rebound effects in and across sectors. Empirical dynamic models (EDMs), a novel methodology in industrial ecology, are applied to the e‐commerce/energy relationship to accommodate for complex system behavior and state‐dependent effects. The results of these data‐driven methods suggest that e‐commerce increases energy consumption mainly through increases in the residential and commercial sectors. These findings contrast with extant research that focuses on transportation effects, which appear less prominent in this investigation. E‐commerce effects also demonstrate state dependence, varying over the magnitude of e‐commerce as a percentage of the total retail sector, particularly in commercial and transportation realms. Assuming these effects will continue in the future, the findings imply that policy makers should focus on mitigating the environmentally deteriorating effects of e‐commerce in the residential sector. However, this investigation cannot provide root causes for the uncovered e‐commerce effects. Robustness of the empirical findings, limitations of the novel EDM methodology, and respective avenues for future methodological and substantial research are discussed.